PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2019 - A.A. Sagung Istri Kania Kosalia; Ni Putu Ayu Kusumawati; Ni Ketut Muliati (UNHI Press, 2022)
Tax avoidance is tax savings by utilizing the provisions in taxation that are carried out legally to reduce the tax burden. This study was conducted to examine the effect of profitability and leverage on tax avoidance in manufacturing companies. The population of this study are manufacturing companies on the Indonesia Stock Exchange in 2016-2019 with 182 companies. The type of research used is quantitative and the sampling technique uses purposive sampling method so that the samples obtained are 240 samples from 60 companies. The analytical method used in this study is the logistic regression method. Based on the results of the analysis test, it is found that profitability has a positive and significant effect on tax avoidance. Meanwhile, leverage has no significant effect on tax avoidance.